Palazzo delle Aquile . Palazzo delle Aquile - Savona, Stefano; Sparatore, Ester; Porto, Alessia (Bortoluzzi, Penelope ; Savona, Stefano, 2011)
Country: France & Italy. Verzio9 FF Submission. Duration: 02:08:00 Palermo, Sicily. A group of homeless people occupy the City Hall and declare that they won't move out until they get a house. The film is the day-by-day chronicle of the month-long occupation by eighteen families. The authorities allow them to stay, and they –advised by some militant legislators – sleep on the benches and in hallways. As time goes by, the internal struggle starts to deteriorate; conviction and ideals start to fight against weariness. A team of filmmakers led by Stefano Savona stayed inside the building throughout the occupation, with unlimited access to both the occupants – who were in permanent assembly – and the increasingly nervous City officials. Palazzo delle Aquile shows the comings and goings of the political negotiations from within; it builds up the suspense as the conclusion approaches, and follows the case to its touching end.